IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH MELALUI PROGRAM BANK SAMPAH DI KECAMATAN KELAPA GADING KOTA ADMINISTRASI JAKARTA UTARA - Ihsan Wahyudin; Ivan Budi Susetyo (Jurnal Ilmu Administrasi Publik, 2025)
Residents in Kelapa Gading District, North Jakarta, face landfill problems because the volume of daily waste in DKI Jakarta continues to increase. In response, the government enacted Law Number 18 of 2008 and Governor Regulation Number 77 of 2020 concerning waste management. This study aims to analyze and evaluate the implementation of waste management policies through waste bank programs in the region. This study used a descriptive method based on a qualitative approach with data collection techniques including observation, interviews, and documentation. The informants consisted of four people, including the head of the Environmental Agency, the Chairman, and members of the waste bank in Kelapa Gading District, as well as a lecturer in public administration. The results showed that the implementation of the Waste Management Policy through the Waste Bank Program in Kelapa Gading District is in accordance with Pergub 77 of 2020 concerning Waste Management for Community Harmony and meets four aspects of research, namely communication, resources, disposition, and organizational structure. However, there are still constraints on communication aspects and resources that need to be improved in order to achieve optimal implementation. Obstacles to implementing the policy include a lack of understanding of the policy, difficulties in program socialization, limited infrastructure, and adequate facilities, as well as the need to increase public awareness and face challenges in monitoring and changing policies. Obstacles to implementing the policy include a lack of understanding of the policy, difficulties in program socialization, limited infrastructure, and adequate facilities, as well as the need to increase public awareness and face challenges in monitoring and changing policies. To overcome obstacles in the implementation of waste management policies through the waste bank program in Kelapa Gading District, efforts need to be made such as increasing inclusive socialization, forming positive examples through pilot waste banks, strengthening supporting infrastructure, and conducting good coordination and supervision.